Hormonal effects on intracellular and secreted casein in cultures of mouse mammary epithelial cells on floating collagen membranes. - Emerman, J T (1977)
Cultured on floating collagen membranes in the presence of lactogenic hormones, dissociated normal mammary epithelial cells from prelactating mice acquire the ultrastructural and biochemical characteristics of differentiated mammary secretory cells in vivo. The cells on floating collagen membranes in medium containing insulin alone have sparse secretory organelles, and a small amount of casein can be detected in these cells with a sensitive radioimmunoassay. These cells resemble counterpart cells in early-pregnant mice. When the cells are exposed to insulin, cortisol, and prolactin, the secretory apparatus is elaborated and significant increases in intracellular and extracellular casein are observed. In this environment, the intracellular casein content is generally four to eight times greater than in freshly dissociated cells or cells cultured in insulin alone. The amount of casein secreted into the medium by floating-collagen-membrane cultures in the three hormones is from 25 to 200 times greater than that secreted by cultures in insulin alone. Cells cultured on plastic substrates in either hormone combination fail to show any increase in intracellular or extracellular casein. On floating collagen membranes, the cells differentiate in response to hormones as they do in vivo and in organ culture. This cell-culture system provides an opportunity to study direct effects of environmental factors on mammary differentiation at the cellular level.